ANALISIS PENGUKURAN KELELAHAN FISIK DAN MENTAL PADA AKTIVITAS MENDAKI GUNUNG (Studi Perubahan Denyut Jantung dan Short Term Memory Pada Aktivitas Pendakian Gunung Ungaran) - , SYUKRAN TRINATA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are many aktivitasekstrim that we often encounter in everyday life.These include gunung.Aktivitas climbing mountain climbing activities can dikatakanaktivitas weight because it requires the ability, strength and high fighting spirit to do so.To examine this, we need a study to determine the level of this kelelahannya.Penelitian analyze the level of physical and mental fatigue on the activity of mountain climbing in the can through at some point measurement with a particular test.This study will also measure the environment to see environmental data research is going on considering environmental factors related to the activity of mountain climbing. The sample used in this study consisted of 4 men aged 21-22 years.Categories sample is purposive sampling where samples were selected that have special abilities.Locations measurements done at Mount Unggaran (2,205 masl), Central Java.Point measurement is performed at 4 height plus the height of the normal, which is at an altitude of 1264 meters above sea level, 1454 meters above sea level, 1616 meters above sea level and 2025 meters above sea level.The measurements were measured 2 times that by the time the activity up and down.Test your heart rate per minute will be used to reference the physical fatigue and short term memory task as mental fatigue, while a reference noise, light, humidity, temperature, distance and altitude to see the data measured environmental factors that occur during a mountain climbing activities. The results of this study states that the average overall percentage of correctly taskshort term memory does not differ much better on the activity of ascending, descending and normal activity.Average heart rate per minute when the numbers rose higher activity than the activity down and normal activities.There are some height where the heart beats per minute it falls under the category of heavy activity so that the rest of t minutes can lower average heart rate per minute up to the light activity category.When the rise of activity, jumlahdenyut heart per minute at an altitude of 2,025 meters above sea level point of magnitude smaller than the jumlahdenyut heart per minute at altitude due to the length of time before a spontaneous break when heading height is the most besardaripada duration of spontaneous breaks another.In addition, the data obtained that moisture is the biggest environmental factor whose value than other environmental factors because its value always is above the 85% figure.